Demystifying the arduous doctoral journey: the eagle vision of a research proposal - Ibrahim, Rahinah (Academic Publishing International, 2011)
In fast-paced business organisations, there is critical need for conducting systematic research in order to explain and solve recurring problems in the industry. However, we find many building professionals losing their patience over the unknown end of a doctoral study as most of them practise problem-solving in their jobs since they were so trained. The purpose of this article is to present a visualisation tool developed by a built environment faculty to explain a typical three-year journey that mature building professionals are required to take for solving their own research inquiries. We claim that if these mature students are given a quick overview on how and what their doctoral journey would involve at the start of their studies, they will be less fearful of uncertainties and will accordingly fulfil the requirements of their doctoral studies successfully. The Eagle Research Design Table (Eagle Table) is a self-filled tool guided by three research question’s constructs. The key to expanding the Eagle Table is identifying these constructs in a research inquiry first. We have established three constructs—“WHO”, “WHAT” and “HOW”—through prolonged participatory experience in teaching research methodology to building professionals. The “WHO” construct refers to the element or subject being used in, or impacted by, the study while the “WHAT” construct refers to the body of knowledge that is required to solve the research inquiry. The final “HOW” construct refers to the action to be taken on the element or subject during the study. In this article, we present how these three research question’s constructs, when presented in a table form, proved to be successful in providing a quick overview of a doctoral study’s journey. Hence, enabling many mature building professionals to persevere in their studies. Consequently, the academic community would benefit from the rich experience and wisdom of their industry partners in handling and tackling recurring problems in the built environment.